2010
DOI: 10.1186/1471-2431-10-69
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with rotavirus infection among children admitted with acute diarrhea in Uganda

Abstract: BackgroundRotavirus remains the commonest cause of severe dehydrating diarrhea among children worldwide. Children in developing countries die more because of several factors including poorer access to hydration therapy and greater prevalence of malnutrition. Hitherto, the magnitude of rotavirus disease in Uganda has remained unknown. This study was therefore done to determine the prevalence and factors associated with rotavirus infection among children aged 3-59 months admitted with acute diarrhea to paediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
4
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 24 publications
11
61
4
2
Order By: Relevance
“…The main transmission route of infectious diarrhea is fecal-oral transmission. Consequently, many studies have conducted analytical investigations of dangerous factors to stop this route of transmission (Dennehy, 2000;Nakawesi et al, 2010;Temu et al, 2012;Wilking et al, 2012); relevant factors include dietary habits, the eating environment, food varieties, eating traditions, food storage conditions, and health and economic conditions. However, our long-term clinical observations have demonstrated that some infectious diarrhea cases are not associated with a suspicious food history or unclean dietary habits.…”
Section: Introductionmentioning
confidence: 99%
“…The main transmission route of infectious diarrhea is fecal-oral transmission. Consequently, many studies have conducted analytical investigations of dangerous factors to stop this route of transmission (Dennehy, 2000;Nakawesi et al, 2010;Temu et al, 2012;Wilking et al, 2012); relevant factors include dietary habits, the eating environment, food varieties, eating traditions, food storage conditions, and health and economic conditions. However, our long-term clinical observations have demonstrated that some infectious diarrhea cases are not associated with a suspicious food history or unclean dietary habits.…”
Section: Introductionmentioning
confidence: 99%
“…25 Uganda and Turkey studies showed that prevalence of rotavirus infection was 45.4% and 44.4%. 26,27 Another hospital based study from India found that about 3.6% of the cases were positive for E. histolytica. No seasonality was observed although in the neighboring tropical country Bangladesh, a typical seasonality of E. histolytica infection was noticed.…”
Section: Aetiologymentioning
confidence: 99%
“…rotavirus annually (with 232,000 deaths occurring in sub-Saharan Africa) 4 . Statistics have shown that about 20% of child death in sub-Saharan Africa occurs in Nigeria [5][6][7] .…”
Section: African Journal Of Reproductive Health September 2017; 21 (3mentioning
confidence: 99%